INTELLECTUAL CAPITAL AND SUSTAINABLE GROWTH RATE OF LISTED SERVICE FIRMS IN NIGERIA (Journal of Global Accounting, 2026)
This study assessed the nexus between intellectual capital and sustainable growth rate of listed service firms in Nigeria for a ten year period covering from 2015-2024. Human capital efficiency, structural capital efficiency and capital employed efficiency were used to proxy Intellectual Capital, while sustainable growth rate served as the dependent variable. In line with the objectives of the study, three hypotheses were formulated.  Ex-Post facto research design was employed. Fifty one (51) quoted service firms constituted the sample size of this study. Secondary data were extracted from the annual reports and accounts of the sampled firms and were analysed using E-Views 10.0 statistical software. The study employed inferential statistics using Pearson correlation and Panel Least Square (PLS) regression analysis. Findings from the empirical analysis showed that human capital efficiency (β1 = 0.065789; p-value = 0.0000), structural capital efficiency (β2 = 0.024239; p-value = 0.0000) and capital employed efficiency (β3 = 0.090735; p-value = 0.0000) have a significant and positive effect on sustainable growth rate. Conclusively, intellectual capital has a positive and significant effect on sustainable growth rate of listed service firms in Nigeria at 5% level of significance. It was recommended inter alia that firms should invest more in Human capital efficiency to improve performance.
Keywords: Intellectual Capital; Return on Investment; Sustainable Growth